Upper Respiratory Microbiota in Relation to Ear and Nose Health Among Australian Aboriginal and Torres Strait Islander Children. (4th January 2021) - Coleman, Andrea; Bialasiewicz, Seweryn; Marsh, Robyn L; Grahn Håkansson, Eva; Cottrell, Kyra; Wood, Amanda; Jayasundara, Nadeesha; Ware, Robert S; Zaugg, Julian; Sidjabat, Hanna E; Adams, Jasmyn; Ferguson, Josephine; et al.
Abstract: Background: We explored the nasal microbiota in Indigenous Australian children in relation to ear and nasal health. Methods: In total, 103 Indigenous Australian children aged 2–7 years (mean 4.7 years) were recruited from 2 Queensland communities. Children's ears, nose, and throats were examined and upper respiratory tract (URT) swabs collected. Clinical histories were obtained from parents/medical records. URT microbiota were characterized using culturomics with Matrix assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) identification. Real-time PCR was used to quantify otopathogen ( Haemophilus influenzae, Streptococcus pneumoniae, and Moraxella catarrhalis ) loads and detect respiratory viruses. Data were analyzed using beta diversity measures, regression modeling, and a correlation network analysis. Results: Children with historical/current otitis media (OM) or URT infection (URTI) had higher nasal otopathogen detection and loads and rhinovirus detection compared with healthy children (all P < .04). Children with purulent rhinorrhea had higher nasal otopathogen detection and loads and rhinovirus detection ( P < .04) compared with healthy children. High otopathogen loads were correlated in children with historical/current OM or URTI, whereas Corynebacterium pseudodiphtheriticum and Dolosigranulum pigrum were correlated in healthy children. Conclusions: Corynebacterium pseudodiphtheriticum and D. pigrum are associated with URT and ear health. The importance of the main otopathogens in URT disease/OM was confirmed, and their role relates to co-colonization and high otopathogens loads. Abstract : In Indigenous Australian children, the 3 main respiratory pathogens are associated with OM, particularly their bacterial loads and co-colonization. Corynebacterium pseudodiphtheriticum and Dolosigranulum pigrum are related to upper respiratory and ear health. This provides potential targets for preventative biotherapeutics.